Pengembangan Usaha UMKM Enyoy Mochi di Desa Kadugede - Finardi, Felix Alexander; Liyanto, Daniel; Anastasya S., Dea Liwarty; Arrafi, Dzulfaqar; Suweco, Ammar Munadi; Wijaya Putri, Ni Made Febryangga; Suwondo, Yohana Devina; Wiradarmo, Aulia Ardista (Journal Pemberdayaan Masyarakat Indonesia, 2025)
Program Community Development II at Universitas Prasetiya Mulya is a community service activity aimed at applying students' knowledge to serve the community, particularly in Kuningan. One of the partners in this program is Enyoy Mochi, started its mochi business in Kadugede since 2018. Founded by Ms. Azka Nur Azizah and her husband, Enyoy Mochi offers 18 mochi flavors. Enyoy Mochi faces challenges in operations, finances, marketing, and human resource management. Universitas Prasetiya Mulya's Community Development II group assists Enyoy Mochi in optimizing mochi dough production processes, designing marketing strategies and branding, enhancingsocial media engagement, and activating Grab services. Additionally, the group provides financial recording , aids in creating SOPs, and employment contracts.